2022
DOI: 10.1200/jco.2022.40.4_suppl.397
|View full text |Cite
|
Sign up to set email alerts
|

Atezolizumab plus bevacizumab in Child-Pugh B advanced hepatocellular carcinoma patients.

Abstract: 397 Background: Atezolizumab plus bevacizumab (Ate/Bev) demonstrated promising efficacy and safety in patients with advanced hepatocellular carcinoma (aHCC) in the phase III IMbrave 150 trial. However, despite the high unmet need in Child-Pugh B patients, this subgroup of patients was not included in this study. Therefore, we aimed to investigate the efficacy and safety of Ate/Bev in Child-Pugh B HCC patients. Methods: This multicenter retrospective study included 27 HCC patients classified as Child-Pugh B wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…In the present study, there were no obviously different clinical features, ORR/DCR and AE profiles, except for maximum intrahepatic tumor size (≥5 cm) ( p = 0.048), appetite loss and edema/ascites between the CP‐A and ‐B groups, though the mPFS and mOS time periods for the CP‐B patients were not sufficient (6.0 and 6.4 months, respectively). Similar results have been reported by Kim (mPFS/mOS = 2.9/6.0 months, n = 37) 36 and D'Alessio (mPFS/mOS = 2.3/6.5 months, n = 18) 37 …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In the present study, there were no obviously different clinical features, ORR/DCR and AE profiles, except for maximum intrahepatic tumor size (≥5 cm) ( p = 0.048), appetite loss and edema/ascites between the CP‐A and ‐B groups, though the mPFS and mOS time periods for the CP‐B patients were not sufficient (6.0 and 6.4 months, respectively). Similar results have been reported by Kim (mPFS/mOS = 2.9/6.0 months, n = 37) 36 and D'Alessio (mPFS/mOS = 2.3/6.5 months, n = 18) 37 …”
Section: Discussionsupporting
confidence: 88%
“…For increasing PPS, introduction of a systemic therapy for patients in better condition with good hepatic function is an important issue, and possible with not only in cases with TKI but also Atez/Bev treatments. As noted in previous reports of mPFS and mOS in CP‐B patients treated with Atez/Bev, 36,37 the present results regarding PFS and OS indicate that the opportunity for migration to post‐progression treatment as well as clinical benefits from sequential post‐progression therapy are reduced in patients with CP‐B as compared to those with CP‐A.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Thereafter, 21 articles were excluded and 15 studies were finally included for meta-analysis (1 clinical trial and 14 observational studies), [13,[23][24][25][26][27][28][29][30][31][32][33][34][35][36] 4 of these being abstracts. [25][26][27][28] Between reviewer agreement for the inclusion process was 0.75 (95% CI, 0.70-0.80), as assessed by the kappa coefficient. There was disagreement with respect to 4 studies and it was resolved by a third reviewer (M.R.…”
Section: Resultsmentioning
confidence: 99%
“…[20][21][22] Regardless the lack of any evidence, it has been widely hypothesized that immunotherapy could potentially have a less pronounced impact on liver function and could be safer for HCC patients with liver dysfunction, resulting in improved survival. However, until now only 1 single-arm clinical trial with nivolumab in first-line or after sorafenib [12] has evaluated this population and some immunotherapy-based regimes [23][24][25][26][27][28][29][30][31][32][33][34][35][36] have assessed this special population and in real-life studies reported heterogeneous results.…”
Section: Introductionmentioning
confidence: 99%